1999
DOI: 10.1094/phyto.1999.89.8.687
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Pathotypic Diversity in Xanthomonas oryzae pv. oryzae in Nepal

Abstract: Among the 171 strains of Xanthomonas oryzae pv. oryzae (the bacterial blight pathogen of rice) collected from eight rice-producing zones in Nepal, 31 molecular haplotypes were distinguished using two polymerase chain reaction-based assays. Six common haplotypes represented nearly 63% of the strains, and some haplotypes were geographically dispersed. Multiple correspondence analysis divided the collection into five putative genetic lineages. Lineages 1, 2, and 4 were the most frequently detected and occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 40 publications
3
63
1
3
Order By: Relevance
“…The relationship between pathotypic and genetic diversity of Xoo strains has been studied mainly based on analyses of differential interactions with resistance genes and DNA fingerprinting using insertion sequences 1,23,26 . The results suggested that some phylogenetic lineages based on insertion sequences were related to pathotypes (races).…”
Section: Insertion Sequencesmentioning
confidence: 99%
“…The relationship between pathotypic and genetic diversity of Xoo strains has been studied mainly based on analyses of differential interactions with resistance genes and DNA fingerprinting using insertion sequences 1,23,26 . The results suggested that some phylogenetic lineages based on insertion sequences were related to pathotypes (races).…”
Section: Insertion Sequencesmentioning
confidence: 99%
“…The transposable element used in these studies was assumed to be phenotypically neutral and suitable for phylogenetic analysis. Adhikari et al 2,3 and George et al 6 also found evidence of the geographic migration of Xoo using multicopy genetic markers. They suggested that the distribution might be through germplasm exchange.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a breeding program should be initiated to transfer these resistant genes from differential varieties to high quality varieties of Vietnamese rice to control the disease effectively. Lee et al 9 and Adhikari et al 2 showed that strains virulent to Xa21 gene were widely distributed in Korea and Nepal. Several strains moderately virulent to Xa21 (of lesion length between 10 and 15 cm) were detected in our limited sample range from northern Vietnam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the durability of resistance depends upon the prevalence of pathogen races in time and space (Jagjeet et al, 2010). This is due to the fact that the pathogen Xoo is highly variable and more than 30 races of the bacterium have been reported worldwide (Adhikari et al, 1999;Noda et al, 2001).…”
Section: Bacterial Leaf Blight (Blb) Of Rice Caused Bymentioning
confidence: 99%